O sujeito e a subjetividade em Luis Alberto Warat: uma análise - Gomes, Joyce Kaynara Silva (2023)
The present work falls within the field of studies on legal subjectivity, more precisely in the establishment of constructions, meanings, and ideas about the subject and subjectivity as categories, based on the work of Luis Alberto Warat, an Argentine jurist and philosopher who made important critical contributions to Legal Science and Law in Brazil, based on his analytical training. The basic assumption for this endeavor is that, through the conventional reading of his work, there is an important production regarding subjectivity (whether sociological, psychological, or juridical), which led to the central question about: what are the articulations and associations made by the author throughout his work regarding the ideas of legal subject and the idea of subjectivity? Thus, the objective of this research was primarily to analyze the categories throughout the work, presenting concepts, discovering and describing characteristics attributed by the author based on the so-called three stages of his intellectual trajectory, namely: analytical semiology, political semiology, and the semiology of desire. Therefore, this is a text resulting from a theoretical and descriptive research that used methodological instruments from Content Analysis, suitable for the handling and interpretation of a corpus composed of ten books. The first chapter is dedicated to an overview of the author and work, which directly impact the interpretation of the corpus, and the second chapter brings the process of organization, systematization and analysis of the books, as well as the limits of the research itself. Next, the third chapter deals with the general understanding of legal subjectivity and the legal subject, with a certain centrality in the ideas brought by Kelsen, operating criticisms of the same from natural law perspective and other theoretical paradigms, such as the subject operated in discourse analysis. The final chapters articulate the findings, that is, what was seen and interpreted, such as the changes in the meaning and application of the categories as the author's ideas mature, the theoretical ruptures with the analytical school, the use of psychoanalytic and related foundations, which manage to situate the subject as “something more than a set of positive norms” and as less than a correspondence to the fleshand-blood human being.